PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWAKELAS IVSDN 014 PEMATANG SIKAT KECAMATAN RIMBA MELINTANG - Afriani '; Zariul Antosa Zariul Antosa; Damanhuri Daud Damanhur Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem this research is the student achivement of IPS Fourth garders studies still low with an average value 6.0 and minimum completeness criteria ( KKM ) IPS is 65. Between students amounting to 25 pepole only 7 students who achieve clasical KKM. This research is classroom action Research ( CAR ). Which aims to improve the student achievement of IPS sudies clas IV at SDN 014 Pematang Sikat with implementation cooperative learning model jigsaw. Formulation of the problem : Is the implementation of cooferative learning model jigsaw can improve students achivement of IPS syudies at SDN 014 Pematang Sikat. Subjects were students Of SDN 014 Pematag Sikat. Totalling 25 people who use the data source, the data collection intruments in this thesis present the result obtained each day before the action improved in base score cycle with the average being 62. In the first cycle improve in average of 70 and an improve second cycle with an average of 76,6. Activities of the teacher in the learning process at the cycle one 62,5% and 79,16% and in the second cycle improved. So the result in class IV SDN 014 Pematang Sikat that the implementation of cooperatiff learning model Jigsaw can Improved the student Achivement of IPS studies at fourth graders SDN 014 Pematang Sikat. Keyword : Cooperatiff learning model Jigsaw,the result of social studies